2020
DOI: 10.1007/s10554-020-02050-w
|View full text |Cite
|
Sign up to set email alerts
|

Automated analysis and detection of abnormalities in transaxial anatomical cardiovascular magnetic resonance images: a proof of concept study with potential to optimize image acquisition

Abstract: The large number of available MRI sequences means patients cannot realistically undergo them all, so the range of sequences to be acquired during a scan are protocolled based on clinical details. Adapting this to unexpected findings identified early on in the scan requires experience and vigilance. We investigated whether deep learning of the images acquired in the first few minutes of a scan could provide an automated early alert of abnormal features. Anatomy sequences from 375 CMR scans were used as a traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Natural language processing can automate clinical documentation by text summarization [ 11 ] and detect diagnoses from scan reports [ 12 ]. Computer vision algorithms can detect lesions from radiological scans, make measurements, and pick-up incidental findings, saving time and reducing error [ 13 , 14 ]. Robots trained by human operators could perform procedures such as venepuncture, and ultrasound [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural language processing can automate clinical documentation by text summarization [ 11 ] and detect diagnoses from scan reports [ 12 ]. Computer vision algorithms can detect lesions from radiological scans, make measurements, and pick-up incidental findings, saving time and reducing error [ 13 , 14 ]. Robots trained by human operators could perform procedures such as venepuncture, and ultrasound [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that deep learning can be used to automatically plan CMR standard view images [20] . Deep learning algorithms can also be implemented to analyze CMR images while the scan is ongoing, and their output is useful to guide selection of scan protocols based on initial findings [21] . However, leveraging AI technology for real-time CMR quality assurance has so far been limited to tissue segmentation and automatic measurements rather than assessing LGE likelihood [22] , [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Preprocessing Ground truth PAT segmentation was semi-automatically performed in 70 training images (Fig 1). As the first step, we identified the cardiac chambers and left ventricular (LV) myocardium using HRNet, an existing CNN trained in T2-weighted images with a similar contrast [11]. Using these segmentations, we created a bounding box around the heart.…”
Section: Methodsmentioning
confidence: 99%
“…Aims In this project, we aim to estimate PATV from clinical CMRI. We focus on axial T2-weighted rapid gradient-echo scans which are routinely acquired in the clinic and in which CNNs have been used to accurately segment several cardiac structures [11]. We initially create a non-learned semi-automatic image processing protocol to segment PAT and generate training data for the proposed CNN.…”
Section: Introductionmentioning
confidence: 99%